Comparative Analysis of Financial Performance of SOE Cement Companies in the Post-Entry of Massive Foreign Capital Companies of Cement Industry in Indonesia - Ahmad Dahlan Malik; Wahyu Agung Handono (Universitas Airlangga, 2018)
In order to achieve the Master Plan for the Acceleration and Expansion of the Indonesian Economic Development (MP3EI) program which has a significant impact on cement demand outside java, it is necessary to improve the performance of cement companies, especially state-owned cement companies consisting of PT Semen Indonesia Tbk (Persero) and PT Semen Batu Raja (Persero). In addition, competition in the globalization era in fulfilling domestic cement is a challenge for state-owned cement companies with Cement Foreign Investment (PMA) industries in Indonesia which are listed on the Indonesia Stock Exchange. To increase attractiveness and strengthen performance, state-owned cement companies need to display an analysis of attractive financial performance along with the selection of independent variables in the discrimination function as a variable that explains precisely the performance of the company based on the Discriminant Stepwise Method. This is in accordance with the purpose of this study by analysing Du Pont System Analysis, Analysis of financial ratios in the form of liquidity ratios, solvability, profitability, activity, along with reference to the Decree of the Minister of Finance of the Republic of Indonesia No. 826/KMK.013/1992, and strengthened by the Decree of the Minister of BUMN No: KEP-100/MBU/2002 in financial aspects for the performance of state-owned enterprises. This study also provides additional analysis in the form of Economic Value Added (EVA), Tobin’s q and Altman Z-Score as a complement to the comparison of the financial performance of state-owned cement companies and Cement PMA companies in the period 2013-2016.